CO2 LASER POWER OPTIMIZATION OF PHOTOACOUSTIC SPECTROMETER AND IT’S APPLICATION TO DETECT AMMONIA GAS (NH 3 ) CONCENTRATION ON ISOTONIC BEVERAGE CONSUMER’S BREATH - Bergitta Dwi Annawati; Mitrayana Mitrayana (Magister Scientiae, 2020)
Performance of photoacoustic spectrometer CO2 laser can be optimized by variation of laser voltage with active laser medium gas compositions include gases He, N2 and CO2. Characterization of photoacoustic spectrometer CO2 laser is done by determined resonance curve, quality factor, noise and lowest detection limit. Photoacoustic spectrometer applied to detect ammonia gas concentration in isotonic beverage. Photoacoustic spectrometer was applied to detect the concentration of ammonia in the isotonic drinks and measuring result using multicomponent-analysis. The lowest detection limit for ammonia gas on line 10R14 obtained at (70 ± 7) ppb with highest laser power obtained at (37 ± 0.1) W and the composition of the active medium gas He, N2 and CO2 30:40:30. The highest concentration of ammonia gas, 0 minute in range of (2.89 ± 0.05) ppm, 30 minutes in range of (4.22 ± 0.05), 60 minutes in range of (5.34 ± 0.05), 120 minutes in range of (5.49 ± 0.05) ppm, 150 minutes in range of (3.62 ± 0.05) ppm and 180 minutes in range of (3.28 ± 0.05) ppm. Changes concentration of ammonia gas result are influenced by the length of time after consuming isotonic beverage.